Iron phosphate material, preparation method of iron phosphate material and lithium iron phosphate material

The preparation of iron phosphate materials with specific structures through steps such as emulsifier treatment and oxidation treatment, which solves the problem of low compaction density of traditional lithium iron phosphate batteries and achieves an increase in battery capacity.

CN119461291APending Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411699463.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18

Smart Images

  • Figure CN119461291A_ABST
    Figure CN119461291A_ABST
Patent Text Reader

Abstract

The invention provides an iron phosphate material, a preparation method of the iron phosphate material and a lithium iron phosphate material, the iron phosphate material is of a flocculent structure with a pore structure, the specific surface area of the iron phosphate material is 8m < 2 > / g-12m < 2 > / g, and the molar ratio of an iron element to a phosphorus element in the iron phosphate material is 0.945-0.955. By regulating and controlling the structure of the iron phosphate material, the specific surface area of the material and the molar ratio of the iron element to the phosphorus element to be within the range respectively, the compaction density (for example, 2.7 g / cm < 3 > or above) of lithium iron phosphate prepared by taking the iron phosphate material as the raw material can be effectively improved, so that the capacity of a lithium iron phosphate battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to an iron phosphate material, a method for preparing the iron phosphate material, and a lithium iron phosphate material. Background Art

[0002] Lithium iron phosphate batteries have the characteristics of good safety, high specific energy and power, and long cycle life. They are widely used in backup power supplies, large-scale energy storage and electric vehicles. With the development of new energy battery technology, people have put forward higher and higher requirements on the capacity of lithium iron phosphate batteries. Lithium iron phosphate batteries are generally composed of positive electrode sheets, negative electrode sheets, diaphragms, electrolytes, shells and other accessories, and the compaction density of the positive electrode active material in the positive electrode sheet affects the capacity of the battery. Lithium iron phosphate with an olivine structure is often used as the positive electrode active material of lithium iron phosphate batteries. At present, the compaction density of traditional lithium iron phosphate is relatively low (for example, about 2.6g / cm 3 ), which limits the increase in the capacity of lithium iron phosphate batteries.

[0003] Therefore, how to increase the compaction density of lithium iron phosphate to increase the capacity of lithium iron phosphate batteries is a problem that needs to be solved urgently. Summary of the invention

[0004] Based on this, the present application provides an iron phosphate material, a preparation method of the iron phosphate material and a lithium iron phosphate material to increase the compaction density of the lithium iron phosphate material and improve the capacity of the lithium iron phosphate battery.

[0005] The first aspect of the present application provides an iron phosphate material, wherein the iron phosphate material is a flocculent structure with a pore structure, and the specific surface area of ​​the iron phosphate material is 8m 2 / g -12m 2 / g, and the molar ratio of iron element to phosphorus element in the iron phosphate material is 0.945-0.955.

[0006] In some embodiments, the porosity of the iron phosphate material is 60%-90%; and / or

[0007] The pore size of the pore structure is 300nm-600nm.

[0008] In some embodiments, the iron phosphate material includes primary particles and secondary particles;

[0009] Optionally, the Dv50 of the primary particles is 5 μm-10 μm;

[0010] Optionally, the Dv50 of the secondary particles is 10 μm-20 μm.

[0011] The second aspect of the present application provides a method for preparing an iron phosphate material, comprising the following steps:

[0012] The ferrous phosphate solution is emulsified by an emulsifier to prepare an emulsion; the emulsifier includes one or more of sodium hydroxymethyl cellulose, sodium hydroxyethyl cellulose and sodium hydroxypropyl methyl cellulose;

[0013] The emulsion is oxidized by using an oxidant to prepare a suspension;

[0014] Separating the solid material in the suspension and performing a roasting treatment to prepare the iron phosphate material;

[0015] The iron phosphate material has a flocculent structure with a porous structure, and the specific surface area of ​​the iron phosphate material is 8m 2 / g-12m 2 / g, and the molar ratio of iron element to phosphorus element in the iron phosphate material is 0.945-0.955.

[0016] In some embodiments, the mass percentage concentration of the ferrous phosphate solution is 5%-10%, and the mass percentage of the emulsifier relative to the mass of the ferrous phosphate solution is 1%-15%; and / or

[0017] The step of emulsifying the ferrous phosphate solution with an emulsifier comprises: adding the emulsifier to the ferrous phosphate solution while stirring the ferrous phosphate solution, and continuing to stir after the addition is completed;

[0018] Optionally, the stirring speed is 500 rpm-3000 rpm;

[0019] Optionally, the stirring time after the emulsifier is added is 30 min to 90 min.

[0020] In some embodiments, the oxidant comprises one or more of hydrogen peroxide, sodium peroxide, sodium hypochlorite and ozone; and / or

[0021] The molar ratio of the oxidant to the iron element contained in the ferrous phosphate solution is (1-5):1; and / or

[0022] The oxidation treatment temperature is 70°C-90°C; and / or

[0023] When performing the oxidation treatment, the oxidant is added to the emulsion for a period of 0.5 h to 6 h.

[0024] In some embodiments, the calcination treatment is performed at a temperature of 300° C. to 800° C. for a time of 1 h to 10 h; and / or

[0025] Before the step of calcining the solid material in the suspension, the method further includes: washing and filtering the suspension, and drying the solid material obtained after filtering;

[0026] Optionally, the volume of deionized water used for washing is 1 to 10 times the volume of the suspension;

[0027] Optionally, the drying temperature is 100°C-150°C.

[0028] In some embodiments,

[0029] The preparation method of the ferrous phosphate solution comprises:

[0030] The iron source and the phosphoric acid aqueous solution are mixed to carry out an iron dissolving reaction;

[0031] Optionally, the iron source includes one or more of red iron oxide, yellow iron oxide, black iron oxide, reduced iron powder and iron ingot;

[0032] Optionally, the mass percentage concentration of the phosphoric acid aqueous solution is 20%-60%;

[0033] Optionally, the temperature of the iron dissolving reaction is 40°C-90°C, and the time is 2h-10h;

[0034] Optionally, the mass percentage of the iron source relative to the mass percentage of the phosphoric acid aqueous solution is 5%-30%.

[0035] The third aspect of the present application provides a lithium iron phosphate material, wherein the raw materials for preparing the lithium iron phosphate material include one or more of the iron phosphate material described in the first aspect of the present application and the iron phosphate material prepared by the preparation method described in the second aspect of the present application.

[0036] In some embodiments, the compaction density of the lithium iron phosphate material is ≥ 2.7 g / cm 3 , 1C discharge capacity ≥148mAh / g.

[0037] The iron phosphate material provided above has a flocculent structure with a porous structure, and the specific surface area of ​​the iron phosphate material is 8m 2 / g-12m 2 / g, the molar ratio of iron to phosphorus is 0.945-0.955; by adjusting the structure of the iron phosphate material, the specific surface area of ​​the material and the molar ratio of iron to phosphorus in the above range, the compaction density of lithium iron phosphate prepared using the iron phosphate material as a raw material can be effectively improved (for example, 2.7g / cm 3 Above), thereby increasing the capacity of the lithium iron phosphate battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0039] Figure 1 This is a scanning electron microscope image of the iron phosphate material prepared in Example 1. DETAILED DESCRIPTION

[0040] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0042] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".

[0043] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0044] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0045] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0046] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0047] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0048] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0049] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0050] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0051] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0052] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0053] The compaction density of conventional lithium iron phosphate is relatively low (e.g., about 2.6 g / cm 3 ), which limits the improvement of the capacity of lithium iron phosphate batteries. Iron phosphate is a precursor for the preparation of lithium iron phosphate, and its own indicators (such as iron-phosphorus molar ratio, specific surface area, etc.) have a great influence on the subsequent performance of lithium iron phosphate (such as compaction density, etc.). Traditional iron phosphate production processes include ammonium method, sodium method, iron method, etc. Among them, the morphology of iron phosphate obtained by sodium method and ammonium method is mostly flaky structure, but it is difficult to obtain a higher compaction density for lithium iron phosphate prepared using iron phosphate with this morphology. If you want to prepare lithium iron phosphate with a high compaction density, a higher calcination temperature is required during the preparation of lithium iron phosphate, but iron phosphide is easily produced at high temperature, resulting in a black film phenomenon in the battery. How to increase the compaction density of lithium iron phosphate to increase the capacity of lithium iron phosphate batteries is a problem that urgently needs to be solved. Therefore, the present application adopts a new iron phosphate preparation process, starting from improving the morphology, specific surface area and iron-phosphorus molar ratio of iron phosphate, to prepare iron phosphate with a specific morphology, a larger specific surface area and a lower iron-phosphorus molar ratio, so as to improve the compaction density of lithium iron phosphate using the iron phosphate and increase the capacity of the battery.

[0054] One or more embodiments of the present application provide an iron phosphate material, wherein the iron phosphate material has a flocculent structure with a pore structure, and the specific surface area of ​​the iron phosphate material is 8 m 2 / g-12m 2 / g, the molar ratio of iron to phosphorus in the iron phosphate material is 0.945-0.955.

[0055] As a non-limiting example, the specific surface area of ​​the iron phosphate material may be, but is not limited to, 8 m 2 / g, 8.2m 2 / g, 8.4m 2 / g, 8.6m 2 / g, 8.8m 2 / g, 9m 2 / g, 9.2m 2 / g, 9.4m 2 / g, 9.6m 2 / g, 9.8m 2 / g, 10m 2 / g, 10.2m 2 / g, 10.4m 2 / g, 10.6m 2 / g, 10.8m 2 / g, 11m 2 / g, 11.2m2 / g, 11.4m 2 / g, 11.6m 2 / g, 11.8m 2 / g, 12m 2 / g or the range between any two of the above specific surface areas, etc. When the specific surface area of ​​the iron phosphate material is within the above range, it is beneficial to the melting of the iron phosphate when preparing the lithium iron phosphate material, thereby increasing the compaction density of the prepared lithium iron phosphate material.

[0056] The molar ratio of the iron element to the phosphorus element in the iron phosphate material can be, but is not limited to, 0.945, 0.946, 0.947, 0.948, 0.949, 0.95, 0.951, 0.952, 0.953, 0.954, 0.955 or a range between any two of the above molar ratios. When the molar ratio of the iron element to the phosphorus element in the iron phosphate material is within the above range, it is beneficial to improve the buckling performance of the prepared lithium iron phosphate material.

[0057] It can be understood that the iron phosphate material has a flocculent structure with a porous structure, and the specific surface area of ​​the iron phosphate material is 8m2 / g-12m2 / g, and the molar ratio of iron element to phosphorus element is 0.945-0.955; by regulating the structure of the iron phosphate material and the specific surface area of ​​the material and the molar ratio of iron and phosphorus elements within the above range, the compaction density of lithium iron phosphate prepared using the iron phosphate material as a raw material can be effectively improved (for example, 2.7g / cm 3 Above), thereby increasing the capacity of the lithium iron phosphate battery.

[0058] In some embodiments, the porosity of the iron phosphate material is 60%-90%; for example, it can be but not limited to 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90% or the range between any two of the above porosities. When the porosity of the iron phosphate material is within the above range, it is beneficial to improve the fluidity of the iron phosphate, thereby enhancing its machinability,

[0059] As a possible implementation, the pore size of the pore structure is 300nm-600nm; for example, it can be but not limited to 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm, 500nm, 520nm, 540nm, 560nm, 580nm, 600nm or a range between any two of the above pore sizes, etc. When the pore size of the pore structure is within the above range, it is beneficial to increase the compaction density of the iron phosphate material.

[0060] In some embodiments, the iron phosphate material includes primary particles and secondary particles.

[0061] In some optional embodiments, the Dv50 of the primary particles is 5 μm-10 μm; for example, it can be but not limited to 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm or a range between any two of the above Dv50, etc.

[0062] In some exemplary embodiments, the Dv50 of the secondary particles is 10μm-20μm; for example, it can be but is not limited to 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 16.5μm, 17μm, 17.5μm, 18μm, 18.5μm, 19μm, 19.5μm, 20μm or the range between any two of the above Dv50, etc.

[0063] It should be noted that the Dv50 mentioned above refers to the particle size corresponding to 50% in the volume distribution. As an example, Dv50 can be conveniently measured using a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method.

[0064] One or more embodiments of the present application provide a method for preparing an iron phosphate material, which can be used to prepare the above-mentioned iron phosphate material. The preparation method comprises the following steps:

[0065] The ferrous phosphate solution is emulsified by an emulsifier to prepare an emulsion; the emulsifier includes one or more of sodium hydroxymethyl cellulose, sodium hydroxyethyl cellulose and sodium hydroxypropyl methyl cellulose; the emulsion is oxidized by an oxidant to prepare a suspension; the solid material in the suspension is separated and roasted to prepare a ferric phosphate material;

[0066] Among them, the iron phosphate material has a flocculent structure with a porous structure, and the specific surface area of ​​the iron phosphate material is 8m 2 / g -12m 2 / g, the molar ratio of iron to phosphorus in the iron phosphate material is 0.945-0.955.

[0067] By using the above emulsifier to emulsify the ferrous phosphate solution, the ferrous phosphate solution can be dispersed into a large number of spherical particles, which is conducive to obtaining spherical ferric phosphate materials.

[0068] The preparation method has a simple process and low cost; when the prepared iron phosphate material is used to prepare lithium iron phosphate, the compaction density of lithium iron phosphate and the capacity of the battery can be significantly improved.

[0069] In some optional embodiments, the mass percentage concentration of the ferrous phosphate solution is 5%-10%; for example, it can be but not limited to 5%, 6%, 7%, 8%, 9%, 10% or a range between any two of the above values.

[0070] In some embodiments, the mass percentage of the emulsifier relative to the mass percentage of the ferrous phosphate solution is 1%-15%; for example, it can be but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or the range between any two of the above percentages, etc. When the amount of the emulsifier is within the above range, it is beneficial to improve the emulsification effect.

[0071] As a possible implementation, the step of emulsifying the ferrous phosphate solution with an emulsifier includes: adding the emulsifier to the ferrous phosphate solution while stirring the ferrous phosphate solution, and continuing stirring after the addition is completed.

[0072] It should be noted that during the emulsification treatment, the emulsifier is gradually added to the ferrous phosphate solution while the ferrous phosphate solution is stirred.

[0073] The emulsification effect can be further improved by adding the emulsifier while stirring.

[0074] In some optional embodiments, the stirring speed is 500 rpm-3000 rpm; for example, it can be but not limited to 500 rpm, 700 rpm, 900 rpm, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 2200 rpm, 2400 rpm, 2600 rpm, 2800 rpm, 3000 rpm or the range between any two of the above speeds, etc. When the stirring speed is within the above range, it is beneficial to improve the emulsification effect.

[0075] In some exemplary embodiments, the stirring time after the emulsifier is added is 30 minutes to 90 minutes; for example, it can be but not limited to 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, or a range between any two of the above times. Continuing to stir for the above time after the emulsifier is added is conducive to obtaining a uniform emulsion.

[0076] As a possible implementation, the oxidant includes one or more of hydrogen peroxide, sodium peroxide, sodium hypochlorite and ozone.

[0077] In some optional embodiments, the molar ratio of the oxidant to the iron element contained in the ferrous phosphate solution is (1-5):1; for example, it can be but not limited to 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or a range between any two of the above molar ratios, etc.

[0078] In some embodiments, the oxidation treatment temperature is 70°C-90°C; for example, it can be but not limited to 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C or a range between any two of the above temperatures, etc. Thus, the oxidation efficiency can be improved and the morphology of the obtained iron phosphate material can be controlled.

[0079] In some optional embodiments, during the oxidation treatment, the time for adding the oxidant to the emulsion is 0.5h-6h; for example, it can be but not limited to 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or a range between any two of the above time lengths, etc.

[0080] It should be noted that, when the oxidation treatment is performed, the oxidant is gradually added to the emulsion.

[0081] In some embodiments, the calcination temperature is 300°C-800°C; for example, it may be but not limited to 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or a range between any two of the above temperatures.

[0082] As a possible implementation manner, the calcination time is 1h-10h; for example, it can be but not limited to 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of the above times.

[0083] It should be noted that the temperature and time of the calcination treatment can be combined in any appropriate manner, and both can be selected from any temperature and time of the calcination treatment described in this article.

[0084] In some embodiments, before the step of calcining the solid material in the suspension, the method further includes: washing and filtering the suspension, and drying the solid material obtained after filtration.

[0085] In some embodiments, the volume of deionized water used for washing is 1 to 10 times the volume of the suspension; for example, it can be but not limited to 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 times or a range between any two of the above values.

[0086] In some optional embodiments, the drying temperature is 100°C-150°C; for example, it can be but not limited to 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or a range between any two of the above temperatures.

[0087] As a possible implementation, the method for preparing the ferrous phosphate solution includes: mixing an iron source and an aqueous phosphoric acid solution and then performing an iron dissolving reaction.

[0088] In some optional embodiments, the iron source includes one or more of red iron oxide, yellow iron oxide, black iron oxide, reduced iron powder and iron ingot.

[0089] As a possible implementation manner, the mass percentage concentration of the phosphoric acid aqueous solution is 20%-60%; for example, it can be but not limited to 20%, 30%, 40%, 50%, 60% or a range between any two of the above values.

[0090] In some exemplary embodiments, the temperature of the iron dissolving reaction is 40°C-90°C; for example, it can be but not limited to 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or a range between any two of the above temperatures.

[0091] As a possible implementation manner, the time of the iron dissolving reaction is 2h-10h; for example, it can be but not limited to 2h, 4h, 6h, 8h, 10h or a range between any two of the above time periods.

[0092] It should be noted that the temperature and time of the iron dissolving reaction can be combined in any appropriate manner, and both can be selected from any temperature and time of the iron dissolving reaction described in this article.

[0093] In some optional embodiments, the percentage of the mass of the iron source relative to the mass of the phosphoric acid aqueous solution is 5%-30%; for example, it can be but not limited to 5%, 10%, 15%, 20%, 25%, 30% or a range between any two of the above percentages, etc.

[0094] One or more embodiments of the present application provide a lithium iron phosphate material, wherein raw materials for preparing the lithium iron phosphate material include one or more of the above-mentioned iron phosphate material and the iron phosphate material prepared by the above-mentioned preparation method.

[0095] As a non-limiting example, the preparation method of the lithium iron phosphate material may include the following steps: grinding and mixing iron phosphate with lithium carbonate material, glucose, and titanium dioxide in a mass ratio of 1:0.32:0.12:0.01, and calcining at 780° C. to obtain the lithium iron phosphate material.

[0096] In some embodiments, the compaction density of the lithium iron phosphate material is ≥ 2.7 g / cm 3 .

[0097] As a possible implementation, the 1C discharge capacity of the lithium iron phosphate material is ≥148 mAh / g.

[0098] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.

[0099] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0100] 1. Preparation of iron phosphate materials

[0101] Example 1

[0102] Take 500g of 25wt% phosphoric acid aqueous solution, mix it with 50g of reduced iron powder, react at 40℃ for 8h, and filter to obtain ferrous phosphate solution. Place the obtained ferrous phosphate solution in a beaker, add 45g of sodium hydroxymethyl cellulose while stirring, the stirring speed is 500rpm, and continue stirring for 30min after the addition is completed to obtain an emulsion. Heat the emulsion to 75℃, take 214g of ozone, and pass it at a rate of 1.78g / min. After the addition is completed, keep the temperature constant for 2h to obtain FePO4·2H2O suspension, take 10 times the deionized water of the suspension for washing, dry at 120℃, and roast at 600℃ for 3h to obtain battery-grade iron phosphate material.

[0103] The iron phosphate material prepared in Example 1 was scanned using a scanning electron microscope, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the iron phosphate material has a flocculent structure with a porous structure.

[0104] Example 2

[0105] Take 500g of 55wt% phosphoric acid aqueous solution, mix it with 30g of reduced iron powder and 51g of ferric oxide, react at 85℃ for 7h, and filter to obtain ferrous phosphate solution. Place the obtained ferrous phosphate solution in a beaker, add 60g of sodium hydroxymethyl cellulose while stirring, and the stirring speed is 3000rpm. After the addition is completed, continue stirring for 90min to obtain an emulsion. Heat the emulsion to 90℃, take 121g of hydrogen peroxide, add it at a rate of 4g / min, keep the temperature constant for 2h after the addition is completed, and obtain FePO4·2H2O suspension. Take 10 times the deionized water of the suspension for washing, dry it at 120℃, and roast it at 600℃ for 3h to obtain battery-grade iron phosphate material.

[0106] Example 3

[0107] The preparation method of Example 3 is similar to the preparation method of Example 1, except that the amount of sodium hydroxymethyl cellulose added in Example 3 is 5 g, and the others are the same.

[0108] Example 4

[0109] The preparation method of Example 4 is similar to the preparation method of Example 1, except that the amount of sodium hydroxymethyl cellulose added in Example 4 is 75 g, and the others are the same.

[0110] Example 5

[0111] The preparation method of Example 5 is similar to the preparation method of Example 1, except that the amount of sodium hydroxymethyl cellulose added in Example 5 is 85 g, and the others are the same.

[0112] Example 6

[0113] The preparation method of Example 6 is similar to the preparation method of Example 1, except that the amount of sodium hydroxymethyl cellulose added in Example 6 is 3 g, and the others are the same.

[0114] Example 7

[0115] The preparation method of Example 7 is similar to the preparation method of Example 1, except that the same amount of sodium hydroxyethyl cellulose is used to replace sodium hydroxymethyl cellulose in Example 7, and the other aspects are the same.

[0116] Example 8

[0117] The preparation method of Example 8 is similar to the preparation method of Example 1, except that the same amount of hydroxypropyl methylcellulose sodium is used to replace hydroxymethylcellulose sodium in Example 8, and the other aspects are the same.

[0118] Example 9

[0119] The preparation method of Example 9 is similar to the preparation method of Example 1, except that the stirring speed when sodium hydroxymethyl cellulose is added in Example 9 is 2000 rpm, and the others are the same.

[0120] Example 10

[0121] The preparation method of Example 10 is similar to the preparation method of Example 1, except that the stirring speed when sodium hydroxymethyl cellulose is added in Example 10 is 3000 rpm, and the others are the same.

[0122] Embodiment 11

[0123] The preparation method of Example 11 is similar to the preparation method of Example 1, except that the stirring speed when sodium hydroxymethyl cellulose is added in Example 11 is 300 rpm, and the others are the same.

[0124] Example 12

[0125] The preparation method of Example 12 is similar to the preparation method of Example 1, except that the time for stirring the ferrous phosphate solution after the addition of the emulsifier is 60 minutes in Example 12, and the other parts are the same.

[0126] Embodiment 13

[0127] The preparation method of Example 13 is similar to the preparation method of Example 1, except that the time for stirring the ferrous phosphate solution after the addition of the emulsifier is 90 minutes in Example 13, and the other parts are the same.

[0128] Embodiment 14

[0129] The preparation method of Example 14 is similar to the preparation method of Example 1, except that the time for stirring the ferrous phosphate solution after the addition of the emulsifier is 20 minutes in Example 14, and the other aspects are the same.

[0130] Embodiment 15

[0131] The preparation method of Example 15 is similar to the preparation method of Example 2, except that the addition rate of hydrogen peroxide in Example 15 is 0.6 g / min, and the others are the same.

[0132] Example 16

[0133] The preparation method of Example 16 is similar to the preparation method of Example 2, except that the addition rate of hydrogen peroxide in Example 16 is 0.33 g / min, and the others are the same.

[0134] Embodiment 17

[0135] The preparation method of Example 17 is similar to the preparation method of Example 2, except that the addition rate of hydrogen peroxide in Example 17 is 12.1 g / min, and the others are the same.

[0136] Comparative Example 1

[0137] The preparation method of Comparative Example 1 is similar to the preparation method of Example 1, except that sodium hydroxymethyl cellulose is not used to emulsify the ferrous phosphate solution in Comparative Example 1, and the other conditions are the same.

[0138] The iron phosphate prepared in Comparative Example 1 is block iron phosphate.

[0139] The specific surface area, molar ratio of iron to phosphorus, porosity, pore size of the pore structure, Dv50 of the primary particles and Dv50 of the secondary particles of the iron phosphate materials prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 1.

[0140] 2. Preparation and performance testing of lithium iron phosphate materials

[0141] The iron phosphate materials obtained in the above embodiments and comparative examples were mixed with lithium carbonate, glucose and titanium dioxide in a mass ratio of 1:0.32:0.12:0.01, and ground and calcined at 780° C. for 3 hours to obtain lithium iron phosphate.

[0142] 1. The compaction density of the lithium iron phosphate prepared in the above-mentioned embodiments and comparative examples was tested by using a lithium iron phosphate graphite powder compaction density meter to test the compaction density.

[0143] 2. Battery capacity

[0144] The discharge specific capacity was tested in accordance with the national standard GB / T 42161-2022. The capacity test results are shown in Table 1.

[0145] Table 1

[0146]

[0147] The molar ratio in Table 1 refers to the molar ratio of iron element to phosphorus element in the ferric phosphate material.

[0148] From the comparison of the results of Examples 1-17 and Comparative Example 1 in Table 1, it can be seen that the present application can effectively improve the compaction density of lithium iron phosphate prepared with the iron phosphate material as raw material and improve the capacity of the lithium iron phosphate battery by regulating the structure of the iron phosphate material and the specific surface area and the molar ratio of iron and phosphorus elements within appropriate ranges.

[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0150] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An iron phosphate material, characterized in that: The iron phosphate material has a flocculent structure with a porous structure, and the specific surface area of ​​the iron phosphate material is 8m 2 / g-12m 2 / g, and the molar ratio of iron element to phosphorus element in the iron phosphate material is 0.945-0.

955.

2. The iron phosphate material according to claim 1, characterized in that The porosity of the iron phosphate material is 60%-90%; and / or The pore size of the pore structure is 300nm-600nm.

3. The iron phosphate material according to claim 1, characterized in that The iron phosphate material includes primary particles and secondary particles; Optionally, the Dv50 of the primary particles is 5 μm-10 μm; Optionally, the Dv50 of the secondary particles is 10 μm-20 μm.

4. A method for preparing an iron phosphate material, characterized in that: The steps include: The ferrous phosphate solution is emulsified by an emulsifier to prepare an emulsion; the emulsifier includes one or more of sodium hydroxymethyl cellulose, sodium hydroxyethyl cellulose and sodium hydroxypropyl methyl cellulose; The emulsion is oxidized by using an oxidant to prepare a suspension; Separating the solid material in the suspension and performing a roasting treatment to prepare the iron phosphate material; The iron phosphate material has a flocculent structure with a porous structure, and the specific surface area of ​​the iron phosphate material is 8m 2 / g-12m 2 / g, and the molar ratio of iron element to phosphorus element in the iron phosphate material is 0.945-0.

955.

5. The preparation method according to claim 4, characterized in that: The mass percentage concentration of the ferrous phosphate solution is 5%-10%, and the mass percentage of the emulsifier relative to the mass of the ferrous phosphate solution is 1%-15%; and / or The step of emulsifying the ferrous phosphate solution with an emulsifier comprises: adding the emulsifier to the ferrous phosphate solution while stirring the ferrous phosphate solution, and continuing to stir after the addition is completed; Optionally, the stirring speed is 500 rpm-3000 rpm; Optionally, the stirring time after the emulsifier is added is 30 min to 90 min.

6. The preparation method according to claim 4, characterized in that: The oxidant comprises one or more of hydrogen peroxide, sodium peroxide, sodium hypochlorite and ozone; and / or The molar ratio of the oxidant to the iron element contained in the ferrous phosphate solution is (1-5):1; and / or The oxidation treatment temperature is 70°C-90°C; and / or When performing the oxidation treatment, the oxidant is added to the emulsion for a period of 0.5 h to 6 h.

7. The preparation method according to claim 4, characterized in that: The calcination temperature is 300°C-800°C and the calcination time is 1h-10h; and / or Before the step of calcining the solid material in the suspension, the method further includes: washing and filtering the suspension, and drying the solid material obtained after filtering; Optionally, the volume of deionized water used for washing is 1 to 10 times the volume of the suspension; Optionally, the drying temperature is 100°C-150°C.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method of the ferrous phosphate solution comprises: The iron source and the phosphoric acid aqueous solution are mixed to carry out an iron dissolving reaction; Optionally, the iron source includes one or more of red iron oxide, yellow iron oxide, black iron oxide, reduced iron powder and iron ingot; Optionally, the mass percentage concentration of the phosphoric acid aqueous solution is 20%-60%; Optionally, the temperature of the iron dissolving reaction is 40°C-90°C, and the time is 2h-10h; Optionally, the mass percentage of the iron source relative to the mass percentage of the phosphoric acid aqueous solution is 5%-30%.

9. A lithium iron phosphate material, characterized in that: The raw materials for preparing the lithium iron phosphate material include one or more of the iron phosphate material as described in any one of claims 1 to 3 and the iron phosphate material prepared by the preparation method as described in any one of claims 4 to 8.

10. The lithium iron phosphate material according to claim 9, characterized in that: The compaction density of the lithium iron phosphate material is ≥2.7g / cm 3 , 1C discharge capacity ≥148mAh / g.

Citation Information

Cited By

  • Lithium iron phosphate material and preparation method thereof, positive plate, battery and power utilization system

    CN120793879A

  • Lithium iron phosphate material, preparation method thereof, positive electrode sheet, battery and power utilization system

    CN120793879B